2007
DOI: 10.1093/geront/47.5.642
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of Agitation and Resident Characteristics in the Nursing Home

Abstract: Purpose: Agitation frequently accompanies cognitive decline among nursing home residents. This study used cross-sectional and longitudinal (up to 18 months) methods to examine agitation among profoundly and moderately impaired residents using both staff report and direct observation methods. Design and Methods: The study included participants (N = 78) from a larger study who completed either 12 or 18 months of data collection. There were four measurement points, each separated by 6-month intervals. We recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…In individuals with dementia, psychosis, hyperactivity, agitation and physical aggression were associated with greater cognitive impairment. 26,35,38,[63][64][65] In contrast, Marin et al found no association in dementia between cognitive impairment and depression, delusion, agitation and irritability. 66 Four studies found that symptoms increased with cognitive decline in the early stages of dementia and were most commonly seen in moderate dementia, followed by a declining or stable course in the final stages of dementia.…”
Section: Cognitive Function and Bpsd Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…In individuals with dementia, psychosis, hyperactivity, agitation and physical aggression were associated with greater cognitive impairment. 26,35,38,[63][64][65] In contrast, Marin et al found no association in dementia between cognitive impairment and depression, delusion, agitation and irritability. 66 Four studies found that symptoms increased with cognitive decline in the early stages of dementia and were most commonly seen in moderate dementia, followed by a declining or stable course in the final stages of dementia.…”
Section: Cognitive Function and Bpsd Developmentmentioning
confidence: 97%
“…66 Four studies found that symptoms increased with cognitive decline in the early stages of dementia and were most commonly seen in moderate dementia, followed by a declining or stable course in the final stages of dementia. 35,63,64,67 Cognitive function at onset of wandering was found to differ by type of wandering behaviour; for example, results suggested that excessive walking was more common in mild dementia, whereas in severe dementia getting lost was more likely. 68 No association was found between cognitive function and depressive symptoms in those with dementia, 69,70 whereas in those without dementia and without depression at baseline, cognitive impairment at baseline was associated with an increase of depressive symptoms over time.…”
Section: Cognitive Function and Bpsd Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, the level of cognitive impairment, activities of daily living (ADL) impairment, and demographic characteristics (e.g., age and sex) represent background factors. These variables were selected as covariates because they have established relationships with both pain and disruptive behaviors [15-18] and may influence the relationship between pain and disruptive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 17 studies that showed a significant relationship between agitation and disease severity, 11 (65%) were cross-sectional and six (35%) were longitudinal. Dementia severity in these 17 studies was evaluated by the Mini-Mental State Examination (MMSE) (n = 4) (Burgio et al, 2007;Hamuro et al, 2007;Kasai et al, 2015;O'Donnell et al, 2007), the Global Deterioration Scale (GDS) (n = 2) (Mulders et al, 2016;Steinberg et al, 2006), the Clinical Dementia Rating Scale (CDR; n = 4) (Helvik et al, 2016;Liu et al, 2007;Selbaek et al, 2014;Tanaka et al, 2015), both the MMSE and CDR (n = 2) (D'Onofrio et al, 2012;Peters et al, 2015), or studies did not specify (n = 5). Of these 17 studies showing significant results, agitation was reported as being measured by the NPI in four studies (Fernandez Martinez et al, 2008;Helvik et al, 2016;Peters et al, 2015;Tanaka et al, 2015), the CMAI in two studies (Mulders et al, 2016;Steinberg et al, 2008), and Behavioral Pathology in Alzheimer's Disease Rating Scale (BEHAVE-AD) in one (Liu et al, 2007).…”
Section: Variations In Natural Progression By Geographical Regionmentioning
confidence: 99%